The Qur’an as a main source of scientific knowledge - Ashimi, Tijani Ahmad (2013)
The holy Qur’an, the main source of Islamic faith is a book believed by Muslims to be of completely divine origin. Muslims believe the Quran to be the book of divine guidance revealed from God to Muhammad through the angel Gabriel over a period of twenty-three years and view the Quran as God's final revelation to humanity. As such, Quran has solutions to all the problems of humanity irrespective of how complex they may be and in what age they occur. It deals with every human life from cradle to death. While some worldviews highly depend on human experience to have solution for scientific knowledge, and while some religious traditions only rely on scientific method(observation, experiment, skepticism, hypothesis and theory)to obtain the knowledge of natural phenomenon, the scripture of Islam (Qur’an) which is also a book of knowledge and science seems to have already proven these scientific fact for long centuries. Thus, this humble paper by adopting textual approach will examine the scientific knowledge vis-à-vis in the Qur’an, with particular reference to embryology and astronomy.